Fictosexuality, Fictoromance, and Fictophilia: A Qualitative Study of Love and Desire for Fictional Characters - Karhulahti, Veli-Matti; Välisalo, Tanja (Frontiers in Psychology, 2021)
Fictosexuality, fictoromance, and fictophilia are terms that have recently become popular in online environments as indicators of strong and lasting feelings of love, infatuation, or desire for one or more fictional characters. This article explores the phenomenon by qualitative thematic analysis of 71 relevant online discussions. Five central themes emerge from the data: 1) confusion of having strong feelings toward a character that one knows to be fictional, 2) experiences of stigma and search for peer support, 3) behaviors that are similar to fan activities, 4) questions of asexuality possibly involving sexual desire for fictional characters, and 5) fictional characters operating as supernormal stimuli. These findings are further discussed and ultimately compared to long-term debates concerning human sexuality in relation to fictional characters in Japanese media psychology. Three contexts for future conversation and research are suggested.